Human Leukocyte Antigen Diversity: A Southern African Perspective. (12th August 2015) - Tshabalala, Mqondisi; Mellet, Juanita; Pepper, Michael S.
Abstract : Despite the increasingly well-documented evidence of high genetic, ethnic, and linguistic diversity amongst African populations, there is limited data on human leukocyte antigen (HLA) diversity in these populations. HLA is part of the host defense mechanism mediated through antigen presentation to effector cells of the immune system. With the high disease burden in southern Africa, HLA diversity data is increasingly important in the design of population-specific vaccines and the improvement of transplantation therapeutic interventions. This review highlights the paucity of HLA diversity data amongst southern African populations and defines a need for information of this kind. This information will support disease association studies, provide guidance in vaccine design, and improve transplantation outcomes.